Design a hand orthosis to aid post-stroke patients with hemiplegia - Oroya Barreto, Jhulino Alexis (2021)
Abstract—Stroke is the third cause of all disabilities for people over 25 years old. Indeed, the percentage of people who suffer from hemiplegia after stroke is higher than 75%. Patients with hemiplegia have considerable difficulty performing activities of daily living, such as feeding or grasping objects. Assistive devices for stroke patients have been developing since a very long time ago; however, some of them are not well accepted by patients because they are not comfortable, wearable, portable, lightweight and useful. This research presents the first version of the design of dynamic orthosis to aid post-stroke patients with hemiplegia to grasp cylindrical and spherical objects. The proposed orthosis was designed by using a cyclic design methodology called Iterative Design which is used for continuous product improvement; moreover, this paper presents a detailed description of the control algorithm and the electromechanical design in which a flexible power transmission element was introduced to perform the opening and closing of the hand. Then, a motion study was performed to determine the range of motion (ROM) of the orthosis. Results show that the orthosis is able to cover 88.8% of the ROM of the metacarpophalangeal (MCP) joint and 72.7% of the ROM of the proximal interphalangeal (PIP) joint. These results indicate that the hand orthosis can assist patients in performing grasping tasks. In addition, the main feature of this orthosis is ergonomic because it was designed using anthropometric measurements of the hand. Other features of the orthosis are lightweight (230 g), portable and easy to use. Index Terms—stroke, hemiplegia, assistive device, hand ortho- sis, dynamic orthoses, static orthoses.